The megabook of fluency : strategies and texts to engage all readers - Rasinski, Timothy V.; Smith, Melissa Cheesman (Scholastic, 2018)
Fluency expert Timothy V. Rasinski teams up with Melissa Cheesman Smith, a veteran fifth grade teacher, to help teachers effectively weave fluency work into their daily reading instruction. The book is packed with engaging text and tools, an assessment scale, and high quality ready-to-use lessons including text phrasing and tonality, echo reading, word ladders, and more! Given the importance of fluency and its pivotal relationship to comprehension and word recognition the potential is high for improving students overall reading achievement, and their performance in other content areas -- Provided by the publisher.